Collagen-hydroxyapatite films: piezoelectric properties - Silva, C. C.; Thomazini, D.; Pinheiro, A. G.; Aranha, N. [UNESP]; Figueiro, S. D.; Goes, J. C.; Sombra, A. S. B. (Elsevier B.V., 2001)
In this paper we report a study of the physicochemical, dielectric and piezoelectric properties of anionic collagen and collagen-hydroxyapatite (HA) composites, considering the development of new biomaterials which have potential applications in support for cellular growth and in systems for bone regeneration. The piezoelectric strain tensor element d(14), the elastic constant s(55) and the dielectric permittivity 8(11), were measured for the anionic collagen and collagen-HA films. The thermal analysis shows that the denaturation endotherm is at 59.47 degreesC for the collagen sample. The collagen-HA composite film shows two transitions, at 48.9 and 80.65 degreesC. The X-ray diffraction pattern of the collagen film shows a broad band characteristic of an amorphous material. The main peaks associated to the crystalline HA is present in the sample of collagen-HA. In the collagen-HA composite, one can also notice the presence of other peaks with low intensities which is an indication of the formation of other crystalline phases of apatite. The scanning electron photomicrograph of anionic collagen membranes shows very thin bundles of collagen. The scanning electron photomicrography of collagen-HA film also show deposits of hydroxyapatite on the collagen fibers forming larger bundles and suggesting that a collagenous structure of reconstituted collagen fibers could act as nucleators for the formation of apatite crystal similar to those of bone. The piezoelectric strain tensor element d(14) was measured for the anionic collagen, with a value of 0.062 pC N-1, which is in good agreement compared with values reported in the literature obtained with other techniques. For the collagen-HA composite membranes, a slight decrease of the value of the piezoelectricity (0.041 pC N-1) was observed. The anionic collagen membranes present the highest density, dielectric permittivity and lowest frequency constant f.L. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: collagen-hydroxyapatite; films; piezoelectric properties